Biblical Money and the Church's Mission in the Digital Age - Guild, Stuart V. (Proceeding National Conference of Christian Education and Theology, 2025)
This article examines the relationship between biblical money principles and the mission of the church in the digital age, focusing on Bitcoin as a form of "biblical money" that transcends the modern fiat money system. Based on Luke 16:9 and teachings such as Leviticus 19:36 and Proverbs 11:1, the author asserts that fair money should reflect honesty, avoid value-stealing inflation, and reduce dependence on debt. Bitcoin is judged to meet the principles of scarcity, fragmentability, portability, and resistance to censorship, making it most in line with biblical values of economic justice. In the Indonesian context, although still limited in regulation, Bitcoin has the potential to be used for the storage of value, funding cross-cultural missions, and empowering churches through decentralized financial technology. This article invites the church to rethink missiological finance by applying biblical money ethics in the midst of global economic challenges.